O continente virtual: geografia do ciberespaço e a adolescência digitalizada - Azevedo, Pedro Luz Soares de (2019)
The increasing use of Information and Communication Technologies (ICTs) have implemented new manners of being in the world. These changes are contained in the new context of computer mediated communication and are driven mainly by the use of social networks and popularized Internet-connected smartphones. Therefore, this work aimed to understand some of the vectors that form the subjective relationship between young people and the use of Information and Communication Technologies (ICTs). Through a panorama of the universe configured by social networks, subject communication and subject formation, the general objective of this research is to problematize the way in which virtual technology has become a line of force in the new regimes of contemporary subjectivation. For that, we studied adolescents from a private school in the city of Caçapava, São Paulo, aged between 14 and 17 years. For data collection, we used the following resources: application of a questionnaire; focus groups and interviews with the teaching staff of the school. At last, we conducted interviews with the adolescents considered by their classmates as the largest users of internet. In addition to the field research at the school, a virtual ethnographic research was carried out, consisting of the systematic analysis of the mentioned sites to understand how young people can be constituted from the exposure to these contents and modes of virtual representation of themselves. From this qualitative study we hope to contribute to the constitution of a richer understanding of the forces that form the new social praxis present in the globalized world. The contributions of Sibilia (2016) and Turkle (2011) were used in data analysis